Waste : consuming postwar Japan - Siniawer, Eiko Maruko (Ithaca ; London, 2018)
"A history of the many and changing ideas of waste in Japan from the mid-1940s to the present"--
Introduction : meaning and value in the everyday -- Imperatives of waste -- Better living through consumption -- Wars against waste -- A bright stinginess -- Consuming desires -- Living the good life? -- Battling the time thieves -- Greening consciousness -- We are all waste conscious now -- Sorting things out -- Afterword : waste and well-being.
First published 2018
Includes bibliographical references (pages 307-387) and index.
AAL
Donated by Embassy of Japan in Bangladesh, Read Japan Project 2025, The Tokyo Foundation, supported by The Nippon Foundation.
Keywords: Consumption (Economics) -- Social aspects -- Japan -- History; Waste minimization -- Japan -- History; Refuse and refuse disposal -- Social aspects -- Japan -- History; Japan -- Economic conditions -- 1945-; Japan -- Social conditions -- 1945-